Civic Knowledge, Skills and Values as Correlates of Undergraduates Civic Engagement in Kwara State - Yusuf, Hamdallat Taiwo; Odutayo, Adesegun Olayide; Akintola, Mubarak Akinsegun (Universitas Pendidikan Indonesia, 2020)
Civic Education is charged in inculcating youths with knowledge, skills and values needed efficiently to contribute to the attainment of a better, improved and civilised environment. This study investigated civic knowledge, skills and values as correlates of undergraduates’ civic engagement in Kwara State. The study was a correlational survey type with the population of all undergraduates in Kwara State. 400 undergraduates constituted the sample of the study. Researchers’ designed questionnaire with reliability index 0.83 was used to elicit relevant data. Percentage was used to answer the 4 research questions raised, while linear regression was used to test the hypothesis postulated at 0.05 significant level. The findings of the study revealed the level of undergraduates’ civic knowledge and values were average, while their civic skill was low. It was recommended that curriculum experts should improve Civic Education curriculum to target the three domains of learning as this will bring about positive nation building.